EFEKTIVITAS PELAKSANAAN FUNGSI LEGISLASI DPRD KABUPATEN LOMBOK UTARA BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2014 TENTANG MPR, DPR, DPD DAN DPRD (STUDI KASUS DI KABUPATEN LOMBOK UTARA) - ASMAYANDI ASMAYANDI; TITIN APRIANI; NI LUH ARININGSIH SARI; SYAIFULLAH SYAIFULLAH (Universitas Mahasaraswati K. Mataram, 2024)
The characteristic that shows a country adheres to democracy is the division of power in administering the state. The Trias Politica presented by Montesquieu consists of the executive function, legislative function and also the judicial function. Then these three functions were institutionalized into three state organs, namely the government as the executive, the judiciary as the judiciary and the parliament as the legislature. The formulation of the problem in this research is: first, how to implement the legislative function of the North Lombok Regency Regional People's Representative Council based on Law no. 17 of 2014 concerning the MPR, DPR, DPRD and DPD?, and secondly, what are the factors that influence the implementation of the legislative function of the North Lombok Regency People's Representative Council? The ineffectiveness of the North Lombok Regency DPRD's legislative function can be assessed from the lack of regional regulations produced by the DPRD Institution itself, because, of the several regional regulations that were formed based on the data above, most of the regional regulations are of a regular nature, namely regulations that are an initiative of the Government. Area. Judging from the regional regulations that have been approved, there are three, namely 1 (one) in 2022 and 2 (two) in 2023. The three regional regulations contained are proposals from the executive or regional government. There are two influencing factors, including: Internal factors, namely, members are less proactive in carrying out the legislative functions of the DPRD, and that the capacity or availability of human resources from the 30 North Lombok Regency DPRD members is still minimal. Meanwhile, external factors, namely, regarding budget support, and social factors in carrying out their function as regional regulation makers, until now cannot be separated from their interaction with the community which has its own characteristics